Treatment of an invasive thymoma-like left innominate venous aneurysm using allogeneic pericardium with continuous horizontal mattress sutures: a case report - Duan, Chao; Wu, Haibo; Xing, Fei; Lang, Matthias; Agrafiotis, Apostolos C.; Takamori, Shinkichi; Yamada, Yosuke; Shanshal, Mohamed; Zhou, Chuanjiang (Journal of thoracic disease, 2025)
Treatment of an invasive thymoma-like left innominate venous aneurysm using allogeneic pericardium with continuous horizontal mattress sutures: a case report
Gesehen am 09.12.2025